Digital Literacy Training and Introduction to Artificial Intelligence Ethics to Realize Digital Literate Teachers: Pelatihan Literasi Digital dan Pengenalan Etika Kecerdasan Buatan untuk Mewujudkan Guru Melek Digital - Fakhri, M. Miftach; Isma, Andika; Hidayat M., Wahyu; Ahmar, Ansari Saleh; Surianto, Dewi Fatmarani (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
The problems identified are the level of digital literacy that needs to be improved and the need for an understanding of AI ethics among teachers, which can hinder the education process in the digital era. The purpose of this service is to improve the digital competence and understanding of AI ethics of teachers, so that they can be more effective in teaching and guiding students towards responsible use of technology. Through an Action Research approach, the teachers were directly involved in the process of improving and developing their skills in digital literacy and scientific article writing. The methods used in this training involved lectures, discussions, and practical exercises using various interactive media such as Quizziz, videos, infographics, and educational games. The training was attended by 35 teachers on 4 March 2024. The results of the training showed a significant increase in participants' knowledge and skills related to digital literacy and AI ethics. In addition, there was a positive shift in attitudes towards the use of digital technology. The implication of the training results is the improvement of education quality in the participating schools, as more digitally literate teachers can be more effective in integrating technology in the learning process. In addition, these teachers can act as agents of change in society, helping to build a community of smart and responsible digital technology users. Abstrak Masalah yang diidentifikasi adalah tingkat literasi digital yang perlu ditingkatkan dan perlunya pemahaman etika AI di kalangan guru, yang dapat menghambat proses pendidikan di era digital. Tujuan Pengabdian ini adalah untuk meningkatkan kompetensi digital dan pemahaman etika AI para guru, sehingga mereka dapat lebih efektif dalam mengajar dan membimbing siswa menuju penggunaan teknologi yang bertanggung jawab. Melalui pendekatan Action Research, para guru terlibat secara langsung dalam proses peningkatan dan pengembangan kemampuan mereka dalam literasi digital dan penulisan artikel ilmiah. Metode yang digunakan dalam pelatihan ini melibatkan ceramah, diskusi, dan latihan praktis dengan menggunakan berbagai media interaktif seperti Quizziz, video, infografis, dan permainan edukatif. Pelatihan ini diikuti oleh 35 guru pada tanggal 4 Maret 2024. Hasil dari pelatihan menunjukkan peningkatan signifikan dalam pengetahuan dan keterampilan peserta terkait literasi digital dan etika AI. Selain itu, terdapat pergeseran sikap yang positif terhadap penggunaan teknologi digital. Implikasi dari hasil pelatihan ini adalah peningkatan kualitas pendidikan di sekolah-sekolah peserta, karena guru yang lebih melek digital dapat lebih efektif dalam mengintegrasikan teknologi dalam proses pembelajaran. Selain itu, guru-guru ini dapat berperan sebagai agen perubahan dalam masyarakat, membantu membangun komunitas pengguna teknologi digital yang cerdas dan bertanggung jawab.